Shakespearean melancholy : philosophy, form, and the transformation of comedy - Bernard, J. F. (Edinburgh critical studies in Shakespeare and philosophy., 2018)
This richly contextualized study of Shakespeare's comic engagement with sadness contends that the playwright rethinks melancholy through comic theatre and conversely, re-theorizes comedy through melancholy.